Fabrication of Eudragit polymeric nanoparticles using ultrasonic nebulization method for enhanced oral absorption of megestrol acetate. (21st April 2018) - Seo, Young Dai; Jin, Su-Eon; Kim, Daehyun; Lee, Don Haeng; Yang, Su-Geun
Abstract: Megestrol acetate (MGA) is used as a progestagen to treat advanced cancers in the breast or uterus and anorexia-cachexia syndrome in cancer patients. Due to its low solubility (BCS class II), MGA bioavailability needs to be enhanced for efficacy and safety. We developed MGA-encapsulated Eudragit ® L100 (EUD) nanoparticles (MGA-EUD (1:1) and MGA-EUD (2:1)) using an ultrasonic nebulization method. MGA-EUD (1:1) and MGA-EUD (2:1) consisted of MGA and EUD at the mass ratios of 1:1 and 2:1. Their physicochemical properties, i.e. particle size, loading efficiency, morphology, and crystallinity were determined. Dissolution tests were performed using USP method II. For pharmacokinetics, they were orally administered at 50 mg/kg to mice. Microcrystalline MGA suspension (MGA-MC, Megace ®, BMS) was used as control. MGA-EUD (1:1) and MGA-EUD (2:1) had a smooth and spherical shape of 0.70 and 1.05 µm in diameter with loading efficiencies of 93 and 95% showing amorphous states of MGA. They significantly enhanced the dissolution potential of MGA. Oral bioavailability of MGA-EUD (1:1) and MGA-EUD (2:1) increased 2.0- and 1.7-fold compared to that of MGA-MC. It suggests that ultrasonic nebulization method for the fabrication of polymeric nanoparticles is a promising approach to improve the bioavailability of poorly soluble drugs.